Characterization of a putative transcription factor gene expressed in the 20-OH-ecdysone inducible puff 74EF in Drosophila melanogaster. - Janknecht, R (1989)
Drosophila melanogaster DNA has been cloned which encompasses the major part of the 20-OH-ecdysone inducible puff 74EF. One 20-OH-ecdysone responsive transcription unit was detected which gives rise to two alternative transcripts. The expression of one transcript in salivary glands of 3rd instar larvae is correlated with the 20-OH-ecdysone induced activity of puff 74EF. Corresponding cDNA analysis indicates that the two transcripts are translated into two different proteins which have alternative amino terminal ends. The carboxy terminal domain of the 74E proteins is similar to the carboxy terminal sequences of ets-oncoproteins suggesting that the 74E proteins represent alternative transcription factors. It is proposed that the activity of the 20-OH-ecdysone inducible puff 74EF leads to a switch in the synthesis of a transcription factor.